2007
DOI: 10.1016/j.adolescence.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Parent involvement in the academic adjustment of Latino middle and high school youth: Teacher expectations and school belonging as mediators

Abstract: A path model based in a theory of social capital was tested with Latino middle school (n=195, 58% female, average 13.8 years of age) and high school students (n=129, 64% female, average 16.8 years of age). Most participants (77%) were immigrants (predominantly from Mexico). Questionnaires assessed student perceptions of parent involvement, school belonging, and academic competence. Teachers rated their expectations for student academic attainment and grades were obtained from school records. Perceived school b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 40 publications
7
95
0
12
Order By: Relevance
“…A positive relationship has also been observed between school attachment/sense of belonging to school and academic motivation (Goodenow, 1993;Hagborg, 1998;Neel & Fuligni, 2013;Sánchez, Colón, & Esparza, 2005). As regards the family, Kuperminc et al (2008) demonstrated that parental involvement may contribute to a child's sense of school belonging, suggesting that parents may also influence students' attachment to school. Bean et al (2006) and Henry et al (2011) found that parental monitoring and parental warmth may also serve as independent predictors on youths' academic outcomes.…”
mentioning
confidence: 88%
“…A positive relationship has also been observed between school attachment/sense of belonging to school and academic motivation (Goodenow, 1993;Hagborg, 1998;Neel & Fuligni, 2013;Sánchez, Colón, & Esparza, 2005). As regards the family, Kuperminc et al (2008) demonstrated that parental involvement may contribute to a child's sense of school belonging, suggesting that parents may also influence students' attachment to school. Bean et al (2006) and Henry et al (2011) found that parental monitoring and parental warmth may also serve as independent predictors on youths' academic outcomes.…”
mentioning
confidence: 88%
“…Lower levels of parental school involvement were linked to decreased educational expectations. For immigrant students, the level of parental school involvement declines as children get older, which is consistent with prior findings (Kuperminc et al, 2007). Difficulties with the English language had a direct effect on the outcome measures.…”
Section: How Do Various Experiences Of Parental Absence Affect Academsupporting
confidence: 81%
“…These include gender of the student (Crul & Vermeulen, 2003;Portes & Rumbaut, 2001;Suarez-Orozco & Qin-Hilliard, 2004;Suarez-Orozco & Carhill, 2008;Suarez-Orozco et al, 2009;Way, 2004), difficulties with the English language (Genesee & Gandara, 1999;Hernandez, 2004;Suarez-Orozco & Carhill;Suarez-Orozco et al, 2009), a problematic school environment (Gaytan et al, 2007;Han, 2008;Suarez-Orozco & Carhill;Woolley, 2007), economic hardship (Garibaldi, 1997;Roscigno, 2000;Suarez-Orozco & Carhill;Suarez-Orozco et al, 2010), and reduced parental involvement in the educational process (Barnard, 2004;Hernandez;Gaytan et al;Kuperminc, Darnell, & Alvarez-Jimenez, 2007;Martinez, DeGarmo, & Eddy, 2004;Suarez-Orozco et al, 2010), as well as coming from a single-parent home (Amato & Sobolewski, 2001;Coley, 1998;Lamb, 1999;Suarez-Orozco et al, 2009;Suarez-Orozco et al, 2010).…”
Section: Academic Achievement Among Spanish-speaking Immigrant Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately they demonstrate lower levels of involvement with their children than native-born parents [2,11,12]. Lower English language proficiency can inhibit parents from performing a number of important activities, such as attending school events and parent-teacher conferences, helping with homework, and reading to their children.…”
Section: Introductionmentioning
confidence: 99%